Implementasi Kurikulum Muatan Lokal Tahfidz Qur’an di SMA Istiqomah Bandung - M, Muhammad Mirwan; Sofia, Wida Nafila (Attractive : Innovative Education Journal, 2020)
educational activities. The local content curriculum includes curricular activities (activities related to the curriculum) which are used to develop student competencies that are tailored to regional characteristics and potential, including regional excellence. The aim of this article was to anlyze how the implementation of local content curriculum Tahfidz Qur'an at Senior High School Istiqomah Bandung, to analyze the obstacles factors in the implementation of the local content curriculum of Tahfidz Qur'an, and to analyze how to face the problem in implementing local content curriculum Tahfidz Qur'an. The researchers used qualitative methods. Using Interview, observation, and documentation data was collected. The result showed that the implementation of local content curriculum at Senior High School Istiqomah Bandung used three methods, namely sabak, sabki, manzil. The evaluation of Tahfidz Qur'an activities was done regularly either daily, weekly, monthly, and in each semester by submitting the real data about assessments and program activities as well as student memorizing developments. In implementing Tahfidz Qur'an, there were several factor obstacles, namely: laziness and lack of enthusiasm in memorizing, lack of concentration and weakness in memorizing. In responding to the existing obstacles, the teacher or ustadz has taken several actions, include providing motivation to keep the spirit of memorizing the Qur'an, giving rewards or gifts, extracurricular Tahfidz Qur'an, and conducting evaluations. Keywords: Local Content Curriculum, Tahfidz Qur’an, Educational Curriculum